PROVISION OF AGRICULTURAL MACHINERY IN UZBEKISTAN AND ITS INITIAL PROBLEMS (Scientific journal of the Fergana State University, 2026)
This scientific article systematically examines the provision of agricultural machinery in Uzbekistan during the еars of Soviet power and the problems that existed in that area. The study also reveals the historical evolution of equipping Uzbek agriculture with machinery and its significance.